Behavior of suprathermal electrons at the Uragan-3M torsatron after RF heating off - Zamanov, N.V.; Pavlichenko, R.O.; Kulaga, A.E. (Вопросы атомной науки и техники, 2016)
For the past decades the microwave radiometry is a routinely used diagnostics to obtain the information on
temporal evolution and radial profile of the bulk electron temperature at Uragan-3M torsatron plasma experiments.
However, in the case of low plasma density operation we observe the high level of electron cyclotron emission at the
frequencies that match the second and third harmonics of the extraordinary mode after RF heating pulse off. This
effect could be explained with the production of the suprathermal electrons. Study of the behavior suprathermal
electrons is of great importance because: (a) suprathermal electrons significantly distort or make it impossible to
measure the thermal electron temperature; (b) such electrons influence the ionization process, the excitation of the
plasma ions and may lead to the occurrence of several plasma instabilities. The present work describes the results of
experimental studies of the behavior of the emission after turning off the RF heat pulse В течение последних десятилетий микроволновая радиометрия  обычно используемая диагностика для
получения информации о временной эволюции и радиальном профиле температуры электронов во время
плазменных экспериментов на торсатроне Ураган-3М. Тем не менее, в случае низкоплотной плазмы при
помощи этой диагностики наблюдается появление излучения после отключения импульса высокочастотного
нагрева. Этот эффект можно объяснить существованием надтепловых электронов. Изучение поведения
надтепловых электронов важно, поскольку: (а) надтепловые электроны существенно искажают или делают
невозможным измерения электронной температуры; (б) такие электроны влияют на процессы ионизации,
возбуждения ионов плазмы и могут приводить к возникновению целого ряда неустойчивостей.
Описываются результаты экспериментальных исследований поведения излучения после выключения
импульса ВЧ-нагрева. Протягом останніх десятиліть мікрохвильова радіометрія є діагностикою, що зазвичай використовується
для отримання інформації про часову еволюцію та радіальний профіль температури електронів під час
плазмових експериментів на торсатроні Ураган-3М. Тим не менш, у випадку низькощільної плазми за
допомогою цієї діагностики спостерігається поява випромінювання після відключення імпульсу
високочастотного нагріву. Цей ефект можна пояснити існуванням надтеплових електронів. Вивчення
поведінки надтеплових електронів важливо, оскільки: (а) надтеплові електрони істотно спотворюють або
унеможливлюють вимірювання електронної температури; (б) такі електрони впливають на процеси іонізації,
збудження іонів плазми і можуть призводити до виникнення цілого ряду нестійкостей. Описуються
результати експериментальних досліджень поведінки випромінювання після вимкнення імпульсу
ВЧ-нагріву.